c + 69 = 183

Fill in here

Finding the unknown term to the sum is calculated by performing the inverse. The known term is subtracted from the sum.

x + 20 = 50

x = 50 - 20

x = 30

Finding the unknown term to the difference is by the sum between the subtractor and the result.

y - 15 = 40

y = 40 + 15

y = 55

Finding the unknown term at multiplication is by dividing the product by the known factor.

z × 4 = 32

z = 32 ÷ 4

z = 8

Site-ul nostru poate rămâne gratuit numai prin afișarea de reclame.

Vă rugăm să ne susțineți prin dezactivarea blocării de anunțuri.